2022
DOI: 10.1002/casp.2616
|View full text |Cite
|
Sign up to set email alerts
|

Direct and imagined contact moderates the effect of need for cognitive closure on attitudes towards women managers

Abstract: This research investigated the relationship between individual preference for the need for cognitive closure (NCC) and attitudes towards women as managers and the moderating role of direct or imagined contact with women leaders. In two studies (total N = 369) collected in different countries and with different methods (Study 1: Italy, correlational; Study 2: U.S., experimental), it was found that the positive relationship between NCC and negative attitudes towards women as managers was moderated by the quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
(100 reference statements)
0
2
0
Order By: Relevance
“…Drawing from a socio-motivational perspective, this research aimed to clarify the mediational role of the implicit person theory [9] on the effect of the need for cognitive closure [8] on the prejudice about the incompatibility of women with leadership roles and the compatibility with followership roles [47]. More precisely, we hypothesized and found that the need for cognitive closure favors the endorsement of entity theories (i.e., the conviction that individuals' attributes are fixed and unchangeable), which, in turn, brings people to believe that women's features are suitable for followership roles but not for leadership roles.…”
Section: Discussionmentioning
confidence: 99%
“…Drawing from a socio-motivational perspective, this research aimed to clarify the mediational role of the implicit person theory [9] on the effect of the need for cognitive closure [8] on the prejudice about the incompatibility of women with leadership roles and the compatibility with followership roles [47]. More precisely, we hypothesized and found that the need for cognitive closure favors the endorsement of entity theories (i.e., the conviction that individuals' attributes are fixed and unchangeable), which, in turn, brings people to believe that women's features are suitable for followership roles but not for leadership roles.…”
Section: Discussionmentioning
confidence: 99%
“…Experience with working with a female boss and attitudes toward female leaders were unrelated in the male sample, however the use of a single, dichotomous variable to assess contact with female leaders may explain the nonsignificant findings for the male sample. Baldner et al (2022) found that quality contact with female managers predicted attitudes toward female managers, but that quantity contact did not in a combined sample of men and women (differences between men and women were not examined). More research is required to determine whether there is a relation between contact with female leaders and attitudes toward women in the military, as well as study intermediary variables that may explain this relation.…”
Section: Introductionmentioning
confidence: 91%